2017
DOI: 10.1038/s41598-017-01899-7
|View full text |Cite
|
Sign up to set email alerts
|

What the skull and scapular morphology of the dugong (Dugong dugon) can tell us: sex, habitat and body length?

Abstract: The dugong (Dugong dugon, Müller) is an endangered marine mammal species. We examined the relationship between sex, habitat and body length based on the skull and scapular morphology and morphometrics of 81 dugong samples in Thailand. A total of 58 parameters from the skull and scapula (25 from the cranium, 23 from the mandible and 10 from the scapula) as well as tusks were used in this study. Data were analyzed by univariate analysis, followed by discriminant analysis and multivariate linear regression. Here … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…The finding of some regional genetic differences agrees with data on other biological parameters. In 2017, Nganvongpanit and colleagues found skull morphometric analyses were 100% accurate in identifying dugongs in the Andaman Sea versus the Gulf of Thailand, and that dugongs living in the Andaman Sea were larger, based on skull size, than those in the Gulf of Thailand 58 . In addition, mineral elements in dugong teeth were significantly different between dugongs in the two habitats 59 .…”
Section: Discussionmentioning
confidence: 99%
“…The finding of some regional genetic differences agrees with data on other biological parameters. In 2017, Nganvongpanit and colleagues found skull morphometric analyses were 100% accurate in identifying dugongs in the Andaman Sea versus the Gulf of Thailand, and that dugongs living in the Andaman Sea were larger, based on skull size, than those in the Gulf of Thailand 58 . In addition, mineral elements in dugong teeth were significantly different between dugongs in the two habitats 59 .…”
Section: Discussionmentioning
confidence: 99%
“…Our study used 6 parameters of the pelvic bone to achieve the highest rate of accuracy for sex identification at up to 92.10%. A previous study involving other bones of the dugong reported an accuracy rate of up to 96.7% for the skull, 81.8% for the cranium, 78.4% for the mandible, and 68.1% for the scapula 19 . A study involving bottlenose dolphins using morphometric data acquired from pelvic bones reported a high accuracy rate of up to 97% 29 .…”
Section: Discussionmentioning
confidence: 89%
“…However, we could not find any significant hallmark for the pelvic bone that could be used for sex identification. Previous studies involving the scapula of the dugong reported a hallmark for sex identification by scapular morphology using the caudal border tubercle and coracoid process at 91.30% and 96.15% accuracy rates for identifying males and females 19 . The morphology of the dugong pelvic bone indicated a high variation in male and female subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In nature, wild dugongs may not have access to as much seagrass or quantities of food available to captive dugongs. Density of dugongs in the habitat also may affect growth rates due to influences on food availability and habitat quality ( Marsh, 1980 ; Nganvongpanit et al, 2017a , 2017b ), which in turn could affect age of sexual maturity. Population differences in age at sexual maturity have been observed in wild dugongs.…”
Section: Discussionmentioning
confidence: 99%